An ethnographic study of knowledge sharing across the boundaries between care processes, services and organisations: the contributions to ‘safe’ hospital discharge - Waring, Justin; Marshall, Fiona; Bishop, Simon; Sahota, Opinder; Walker, Marion F.; Currie, Graeme; Fisher, Rebecca J.; Avery, Tony J. (NIHR Journals Library, 2014)
Background